Assessing the potential interaction between CBD and TBR1 CBD and T-box domain - Blignaut, Chanel (University of the Witwatersrand, Johannesburg, 2024)
In 2020, Cannabidiol (CBD) emerged as the most commonly used recreational substance among pregnant women and was perceived as a natural and safer option for alleviating pregnancy- related symptoms, yet its potential effects on foetal neurodevelopment remain uncertain. With varied results from existing literature on the association between prenatal cannabis use and Autism Spectrum Disorder (ASD) development, this study focuses on filling these knowledge gaps. It investigates the potential interaction of CBD with the T-box domain of TBR1, a transcription factor implicated in ASD. CBD may cross the placenta and distribute throughout the developing foetal organs, including the brain, where it may interact with TBR1. This study's objective is to lay the groundwork for future research into the impact of CBD binding on TBR1 functionality, whose dysregulation is implicated in ASD. The study aims to use in vitro and in silico methods to identify and characterise the interaction between CBD and TBR1 T-box Domain. Initially, predictive models were utilised to determine the structure of the TBR1 T-box domain and its binding domains. Subsequently, the ADMET properties of CBD are assessed to determine its potential interaction with TBR1 T-box domain within the body. Through the optimisation of the TBR1 T-box domain and CBD structures, induced fit docking and molecular dynamics simulations, the study aims to predict the potential interaction sites, dynamics and stability of this interaction. The study confirms the computational results using in vitro methodologies. After expressing and purifying the TBR1 T-box domain, a pull-down assay (PDA), thermal shift assay (TSA) and Time-resolved Fourier-transformed infrared spectroscopy (TR-FTIR) are used to evaluate the potential binding, stability and physiochemical properties of the interaction. Computational analysis, using Maestro Schrödinger Induced Fit Protocol, predicts that CBD binds stably within a hydrophobic pocket of TBR1 T-box domain, away from its DNA-interacting residues. Pose 2 and 3 from molecular docking shows the highest binding affinity and molecular dynamics simulations, using Maestro Schrödinger Desmond Molecular Dynamics System, reveal that the TBR1 T-box domain stabilises upon interaction with CBD. Specifically, the interaction is facilitated by hydrophobic interactions and hydrogen bond formation with residues Ser238, Pro335, Thr360, Glu363 and Asn240. Experimental validation through PDA and TSA provided inconclusive results, but TR-FTIR confirmed the dynamic nature of the CBD-TBR1 interaction, characterised by time-dependent spectral changes. While the results do not directly indicate an impact of CBD on TBR1 functionality, further DNA binding studies are necessary for confirmation. This study suggests caution in using CBD during pregnancy due to its complex and largely unexplored interaction with TBR1, underscoring the need for more comprehensive research to conclusively understand its influence on neurodevelopmental disorders and its therapeutic potential
A Dissertation submitted in fulfillment of the requirements of the degree of Masters of Medicine to the Faculty of Health Science, School of Public Health, University of Witwatersrand, Johannesburg 2024
Keywords: Cannabidiol (CBD); UCTD; Autism Spectrum Disorder (ASD); TBR1; SDG-3: Good health and well-being